Real‐Time Super Resolution for 4K2K TVs using Edge Directed Unsharp Masking Sharpening Method. Issue 1 (June 2014) - Lin, Fang‐Cheng; Peng, Kuo‐Shiuan; Huang, Yi‐Pai; Shieh, Han‐Ping D.
Abstract We proposed an efficient edge directed unsharp masking sharpening (EDUMS) method to achieve real‐time super resolution for a 4K2K TV application. Based on conventional unsharp masking sharpening, EDUMS used simple and robust edge information to reproduce clear edge structure and vivid details of high resolution images with minimum ringing and jaggy artifacts.